2018
DOI: 10.3389/fpsyg.2018.00530
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, Challenge, and Psychophysiological Activation in Therapist–Client Interaction

Abstract: Two central dimensions in psychotherapeutic work are a therapist’s empathy with clients and challenging their judgments. We investigated how they influence psychophysiological responses in the participants. Data were from psychodynamic therapy sessions, 24 sessions from 5 dyads, from which 694 therapist’s interventions were coded. Heart rate and electrodermal activity (EDA) of the participants were used to index emotional arousal. Facial muscle activity (electromyography) was used to index positive and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…Peräkylä et al 2008;Madill 2015), covering such practices as delivery and reception of reformulations of the patient's talk (Antaki 2008), interpretations (Bercelli et al 2008;Peräkylä 2010 and, mirroring of voice between the therapist and the patient (Weiste & Peräkylä 2014), affiliation ruptures (Muntigl et al 2013;Muntigl & Horvath 2014) and even dream interpretation (Peräkylä & Bergmann in review). Quite recently, the conversation analytical account of psychotherapy has been linked to the measurement of the physiological responses in the participants of therapeutic sessions (Voutilainen et al 2018). I fully agree with Wooffitt that this line of study could be very informative for the intersubjective psychoanalysis.…”
Section: Between Sociology and Psychoanalysismentioning
confidence: 81%
“…Peräkylä et al 2008;Madill 2015), covering such practices as delivery and reception of reformulations of the patient's talk (Antaki 2008), interpretations (Bercelli et al 2008;Peräkylä 2010 and, mirroring of voice between the therapist and the patient (Weiste & Peräkylä 2014), affiliation ruptures (Muntigl et al 2013;Muntigl & Horvath 2014) and even dream interpretation (Peräkylä & Bergmann in review). Quite recently, the conversation analytical account of psychotherapy has been linked to the measurement of the physiological responses in the participants of therapeutic sessions (Voutilainen et al 2018). I fully agree with Wooffitt that this line of study could be very informative for the intersubjective psychoanalysis.…”
Section: Between Sociology and Psychoanalysismentioning
confidence: 81%
“…Cl: It feels a l(hoh)ot unc(huh)omfortable actually (Rae, 2008, p. 64) Rae speaks of 'lexical substitutions' that have the effect that a patient can admit to have downgraded his feelings in his utterances. Such lexical substitutions show that not only therapists do 'understand' (Madill, 2015) that therapists are not simply 'empathic', but they 'challenge' their clients' self-descriptions (Voutilainen et al, 2018). Challenging is the other pole of the continuum.…”
Section: Extractmentioning
confidence: 99%
“…Research in CA has begun to shed light on how empathy is practiced by psychotherapists in the context of psychotherapeutic interactions (Hutchby 2005;Voutilainen et al 2018;Peräkylä 2011;Weiste & Peräkylä 2013;Wynn and Wynn 2006). Researchers who examined empathy in psychotherapy under CA framework in past studies reported mostly on a threepart sequence (Muntigl et al 2014;Wynn and Bergvik 2010), examined psychotherapists' practices to express display (Muntigl et al 2014) and tested the effect of empathy on psychophysiological responses in participants (Voutilainen et al 2018). To the best of my knowledge, little work has been done to examine organizational features and turn design of empathy in psychotherapy, and no studies have touched on turn constructions of empathic talk by which psychotherapists convey empathy towards their clients' troubles/feelings talk.…”
Section: Conversation Analytical Studies On Empathy In Interactionmentioning
confidence: 99%